Biosolids: What are the different types of reuse?. (20th November 2019) - Collivignarelli, Maria Cristina; Canato, Matteo; Abbà, Alessandro; Carnevale Miino, Marco
Abstract: In recent years, rapid population growth and industrialization have increased the use of natural resources and the production of waste. To develop a circular economy, it is necessary to study and promote alternative long-term solutions for waste disposal, such as reuse and recovery. Wastewater treatment plants (WWTPs) can be an important part of circular sustainability if re-oriented to function as a water resource recovery facilities (WRRFs). In this context, biological sewage sludge (SS) can be treated in order to produce more stabilized residues: biosolids (BS). This paper aims to review the possible alternatives to reuse the BS in order to increase matter recovery. Around 250 papers, reviews, books and conference proceedings have been examined. Authors explored the application of BS on land, such as soil amendment/fertilizer both in agriculture and for interventions on abandoned mine sites, and on engineering fields, in partial or total substitution of virgin materials. The reuse of BS as adsorbent materials and as a source of phosphorus is also discussed. Highlights: Population perceives the reuse of biosolids as dangerous for human and environment. In agricultural reuse of biosolids, heavy metals effects continue to be studied. Feasibility of the utilization of biosolids for brick construction. Conversion into adsorbent material and source of phosphorus is also presented. Further investigation on emerging organic contaminants would be conducted.